Resíduos de sisal na biossorção de metais pesados em solos do semiárido - Silva, Mateus Guimarães da (2023)
Biosorption is a technique that uses materials of biological origin to accumulate contaminants and represents an alternative for the treatment of soils contaminated by heavy metals. The use of residues from the processing of sisal fibers in the biosorption of heavy metals in the soil can result in the reduction of environmental impacts caused by these elements and add economic value to waste that is underused. The objective of this work was to chemically and structurally characterize sisal waste, determine the maximum capacity for adsorption of metals by the waste and their potential for the biosorption of heavy metals in different soils and relate the adsorption of these ions to the characteristics of the waste. Adsorption tests were conducted using the batch method, with electrolyte solutions with increasing monometallic concentrations of Cd and Pb.Then, the data were adjusted to the Langmuir adsorption isotherm models. In a greenhouse experiment, we exposed the Sorghum bicolor plants to different types (mucilage <MUC=, fibrils <FIB= and fiber dust <FD=) and levels of residues of sisal (0.0; 0.5; 1.0; 2.0 and 3.0% w/w) for 60 days. Experiments were also conducted with different soils for 120 days to evaluate the bioavailability and solubility of Cd2+ and Pb2+. The data obtained were subjected to analysis of variance, the means compared using the Scott-Knott test, and the quantitative data were analyzed using regression analysis, at 5% probability. Additionally, multivariate discriminant and principal component (PCA) analyzes and Spearman correlation analysis were performed between lignocellulosic parameters of sisal residues applied to the soil and the bioavailability of heavy metals. The FIB and MUC residues presented a greater adsorption capacity for Cd2+ and Pb2+, while FD presented a higher adsorption energy. The application of FIB and MUC residues to the soil was able to reduce the available levels of Cd2+ and Pb2+ by up to 40%, and the soluble levels in the soil by more than 90%. In addition to the lower levels and accumulations of Cd in the roots and shoots, the application of residues increased dry mass of the plants. A strong correlation of Cd2+ and Pb2+ was observed with the lignocellulosic parameters of the waste. Our results suggest that the application of residues decreases the availability and solubility of Cd2+ and Pb2+ in the soil solution, alleviates phytotoxicity, maximizes plant development in contaminated soils and demonstrates the great potential of residues in mitigating environmental impacts.